RANCANG BANGUN APLIKASI PENGINPUTAN DATA SENSUS PENDUDUK BERBASIS DEKSTOP - Don Avian Safitri (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
The existence of information technology has led to the emergence of various innovations in all fields, one of which is tchnology. This research aims to design an application system for dekstop-based population cencus data collection in Kedunggede Village. By using the literature study method in adding references and this research focuses on designing a cencus data input appliucation data. The features that are applied can be easily understood by users in their use. This application is designed using the C# programming language by utilizing Microsoft Visual Studio software.